Application of the Realistic Mathematical Education (RME) Approach to the Operational Material of Addition of Fractions to Increase Activities and Learning Outcomes of Elementary School Students - Arni, Arni; Nurhayadi, Nurhayadi; Ismaimuza, Dasa (FKIP Universitas Tadulako, 2023)
This study aims to describe the application of the RME approach in increasing student activity and learning outcomes in the material for adding fractions for class V SD Inpres 3 Birobuli. This research uses classroom action research (PTK) which refers to Kemmis and Mc.Taggart Data collection techniques used were tests, observations, interviews, and field notes. The results showed that the application of the RME approach could increase student learning activities and results in the material for addition operations for class V SD Inpres 3 Birobuli by following the steps of the RME approach; (1) understand contextual problems, (2) explain contextual problems, (3) solve contextual problems, (4) compare and discuss student answers, and (5) conclude problems. This research was conducted in two cycles. The results showed that there was an increase in activity and learning outcomes which were seen in the observation of teacher activity in the very good category, student activity in the very good category, student activity in the very active category, and student affective learning outcomes were good. habits, and psychomotor learning outcomes of highly skilled students in cycle II. Likewise, the results of students' final tests with a percentage of learning completeness of 85% in cycle II.